THE KAFAAH CONCEPT OF THE SAKINAH FAMILY IN MUSLIM GENERATION BASED ON ISLAMIC LAW - Muklisin Muklisin (Jurnal Pembaharuan Hukum, 2023)
The idea of the sakinah family in the current Muslim generation. This study aims to explain the meaning of the Sakinah family as one of the aims of marriage mentioned in the Qur'an. The aim of the research is to get ideas that can be used in contemporary life besides having a deep understanding of the substantive meaning of the term. The approach method used in this research is normative juridical. The results of the study state that a sakinah family is a family that maintains harmony, peace, and comfort and operates according to legal and religious principles based on the findings of an examination of a number of concepts by contemporary interpreters. Every prospective husband and wife must make early preparations for their marriage, especially those involving moral, material, mental and spiritual abilities, and must be determined to build and maintain family continuity in accordance with religious and social norms in order to realize sakinah family.